Kyai's Leadership in Prayer-Based Counseling at Pesantren: A Management Strategy - Ainur Rofiq; Moch. Sya'roni Hasan; Loso Judijanto; Suprihatin; Mohd Kasturi Nor Abd Aziz (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
This study explores the implementation of prayer-based counseling at Pondok Pesantren Al Urwatul Wutsqo Jombang under the leadership of the Kyai, and its impact on students' spiritual, emotional, and academic development. Using a qualitative case study approach, data were collected through participant observation, in-depth interviews, and documentation analysis. Findings reveal that structured prayer-based counseling sessions are central to Kyai’s strategy, fostering discipline and reinforcing spirituality. Personalized individual counseling sessions address students' unique challenges, promoting trust and respect. Kyai’s holistic approach involves continuous interaction and collaboration with teachers, ensuring comprehensive support for students' spiritual, emotional, and psychological needs. Integration of traditional Islamic teachings with modern educational practices prepares students for both religious and secular life. The study highlights significant improvements in student behavior and academic performance attributed to the spiritual and emotional support provided by Kyai. Despite its limitations, including the focus on a single pesantren and reliance on qualitative data, the study offers valuable insights into effective leadership strategies within Islamic educational contexts. These findings contribute to the field of spiritual counseling, providing practical guidelines for educators and leaders in similar settings..